(untitled) (Global Journal of Management and Business Research, 2019)
Flagship regeneration as a model of urban renewal materialized in search for pragmatic solutions to the socioeconomic problems caused by deindustrialisation of some ancient cities in the United Kingdom and United States of America late 1960s The subsequent adoption of this concept by other developed countries was due to its capability as panacea to city decay and ability to revitalize or rebrand urban centre for investment attractions and possibility of reducing the burden of social services provision on the municipal governments The reviewed literatures explain that individual city has basic features or attributes upon which flagship projects could be developed and thereby accord such city with unique image and functionality within and outside the region Also the possible drive for wealth creation and eventual poverty alleviation edged flagship regeneration over other contemporary models of urban renewal However despite the acclaimed age long benefits of flagship projects there have been no appreciable efforts by the Nigerian government to embrace or encourage this concept even at the abundance of potentialities The paper therefore examines the application of flagship regeneration in the UK and USA with a view to establishing its prospect in proffering solutions to urban degeneration in Nigeria In this course the diversity of cultural background historical heritage job specialisation fascinating Mother Nature etc are perceived to be reference points for tourism flagships development Conversely an indepth exploration unfolds various peculiar encumbrances that could undermine its smooth application It was however concluded that various tiers of governments should embrace flagships development with due attention to the recommendations made for surmounting the envisaged bottlenecks and ensuring resourceful implementation